Edible films and coatings based on agrifood residues: A new trend in the food packaging research - Gaspar, Marisa C (2023)
Food packaging trends have been changing in the last years, mainly due to consumer concerns about plastic pollution and agrifood waste. Recent advances in the development of edible films and coatings are discussed. These systems can be much more than packaging, with additional functions such as antioxidant, antimicrobial, and nutritional properties, among others. Challenges in industrial processes and/or in some films’ properties are addressed from the authors’ point of view. The use of agrifood residues in these packaging systems is included as a promising strategy that promotes sustainability and circular economy. The authors consider that more research and actions are needed to achieve the best packaging material for each food product with reduced production costs.